2018
DOI: 10.1007/s12275-018-7488-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of high-salinity stress for enhancing the lipid productivity of Chlorella sorokiniana HS1 in a two-phase process

Abstract: Increased lipid accumulation of algal cells as a response to environmental stress factors attracted much attention of researchers to incorporate this stress response into industrial algal cultivation process with the aim of enhancing algal lipid productivity. This study applies high-salinity stress condition to a two-phase process in which microalgal cells are initially grown in freshwater medium until late exponential phase and subsequently subjected to high-salinity condition that induces excessive lipid acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…This happened as Chlorella can easily grow either in freshwater or brackishwater. High salinity level in the brackishwater induces lipid formation in Chlorella cells (Kakarla et al, 2018), making Chlorella retain the osmoregulation process with the lipid protection on the cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…This happened as Chlorella can easily grow either in freshwater or brackishwater. High salinity level in the brackishwater induces lipid formation in Chlorella cells (Kakarla et al, 2018), making Chlorella retain the osmoregulation process with the lipid protection on the cell walls.…”
Section: Resultsmentioning
confidence: 99%
“…While high salinity stress strongly influences the viability and biochemical composition of algal crops and thus the economic feasibility of entire algal biorefinery (Kakarla et al, 2018; Laurens et al, 2017; Oh et al, 2019), this study was set out to elucidate transcriptional responses that give rise to the salt tolerance of highly-productive Chlorella sp. HS2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kakarla et al supplemented 60 g/L of NaCl into concentrated Chlorella cultures for 48 hr and reported ca. 58% increase in algal lipid productivity, supporting the possibility of deploying high salinity stress as a promising post-treatment for the cultivation systems targeting to produce algal lipids (Kakarla et al, 2018). Moreover, while high salinity stress could act as an effective method of crop protection in reducing freshwater cyanobacterial or ciliate contaminants, it was successfully demonstrated to facilitate algal harvesting by enlarging cellular diameter and increasing algal settling rates (Church et al, 2017; Lee et al, 2016; von Alvensleben, Stookey, Magnusson, & Heimann, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, studies carried out by Sang-Il et al (2019), showed that by evaluating different operating conditions such as the intensity of LED lights (blue, red, and white) on the cultivation of microalgae like D. salina, different beta-carotene productivity were obtained (Sang-Il et al, 2019). The responses of microalgae could include enhanced metabolism due to increased nutrient (Seung Won et al, 2010) Additional studies showed that Chlorella strain hyper-accumulates lipids under high-salinity stress condition; however, it was found that the high-salinity condition significantly limited the production of algal biomass (Kakarla et al, 2018).…”
Section: Fermentationmentioning
confidence: 99%